Pro-inflammatory endothelial cell dysfunction is associated with intersectin-1s down-regulation - Singla, Sunit (BioMed Central, 2011)
BACKGROUND: The response of lung microvascular endothelial cells (ECs) to lipopolysaccharide (LPS) is central to the pathogenesis of lung injury. It is dual in nature, with one facet that is pro-inflammatory and another that is cyto-protective. In previous work, overexpression of the anti-apoptotic Bcl-X(L) rescued ECs from apoptosis triggered by siRNA knockdown of intersectin-1s (ITSN-1s), a pro-survival protein crucial for ECs function. Here we further characterized the cyto-protective EC response to LPS and pro-inflammatory dysfunction. METHODS AND RESULTS: Electron microscopy (EM) analyses of LPS-exposed ECs revealed an activated/dysfunctional phenotype, while a biotin assay for caveolae internalization followed by biochemical quantification indicated that LPS causes a 40% inhibition in biotin uptake compared to controls. Quantitative PCR and Western blotting were used to evaluate the mRNA and protein expression, respectively, for several regulatory proteins of intrinsic apoptosis, including ITSN-1s. The decrease in ITSN-1s mRNA and protein expression were countered by Bcl-X(L) and survivin upregulation, as well as Bim downregulation, events thought to protect ECs from impending apoptosis. Absence of apoptosis was confirmed by TUNEL and lack of cytochrome c (cyt c) efflux from mitochondria. Moreover, LPS exposure caused induction and activation of inducible nitric oxide synthase (iNOS) and a mitochondrial variant (mtNOS), as well as augmented mitochondrial NO production as measured by an oxidation oxyhemoglobin (oxyHb) assay applied on mitochondrial-enriched fractions prepared from LPS-exposed ECs. Interestingly, expression of myc-ITSN-1s rescued caveolae endocytosis and reversed induction of iNOS expression. CONCLUSION: Our results suggest that ITSN-1s deficiency is relevant for the pro-inflammatory ECs dysfunction induced by LPS.